Organization and Revolution : Working Class Associations in the German Revolutions of 1848-1849 - Noyes, Paul Horning (Book collections on Project MUSE., 1966)
Unlike previous histories which have generally described the uprisings of 1848-1849 as revolutions of "intellectuals," this shows that it was the economic distress of artisans and skilled craftsmen that caused them.Originally published in 1966.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.